Juridical Review of Personal Data Protection in Money Transactions Fund Application - Bagas Mulya Putra; Diana Setiawati (Proceeding International Conference Restructuring and Transforming Law, 2023)
This research discusses the Protection of Personal Data of DANA Digital Wallet Users. DANA is one of the benefits of technological developments. There are negative effects of technological developments, one of which is data leakage. Moreover, DANA is a financial transaction application. Although the development of information technology and the digital economy is very rapid, research related to law and technology in general and the protection of privacy rights has not been too much. Currently, Indonesia has regulations related to personal data protection. The purpose of this study is to determine the protection of personal data of DANA digital wallet users and the responsibility for personal data. The research method used in this study is Normative research, the data used is secondary data. Data obtained through literature studies are then processed through qualitative descriptive analysis. The results of this study show that there are some DANA digital wallet users who do not read the terms and conditions that apply in using DANA. Indonesia has protected personal data through Law Number 27 of 2022 concerning Personal Data Protection. The regulation also describes the efforts made when personal data is misused.